Erratum: Exome-sequencing in a large population-based study reveals a rare Asn396Ser variant in the LIPG gene associated with depressive symptoms - Amin, N; Jovanova, O; Adams, H H H; Dehghan, A; Kavousi, M; Vernooij, M W; Peeters, R P; de Vrij, F M S; van der Lee, S J; van Rooij, J G J; van Leeuwen, E M; Chaker, L; et al. (Molecular psychiatry, 2017)
Correction to: Molecular Psychiatry advance online publication, 19 July 2016; doi:10.1038/mp.2016.101 In the abstract, the P-value of the white matter lesions should have been listed as 3.3 × 10−02. Also in the abstract, the higher risk of Alzheimer’s disease should have been listed as an odds ratio, not an odds ration.